Carbon source utilization pattern of soil bacterial microbiome of bambara groundnut rhizosphere at the different growth stages determines soil fertility - Ajilogba, Caroline Fadeke; Habig, Johan; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
The diversity of microbes in the soil of plants is important for sustainable agriculture as these microbes are important in carrying out different functional processes to improve the soil and invariably plant growth. Inversely the presence of the crop also affects the types of microbial communities in the soil. In this study, bambara groundnut was grown during the planting season in South Africa, from November to March 2014/2015 and 2015/2016 and soil samples were taken after every four weeks after planting. Soil samples were taken 15 cm deep from 2 different landraces named VBR and VL. Microbial diversity was determined by soil microbial Carbon Source Utilisation Profiles (CSUP) using BIOLOG TM GN2 plates. The abundance and richness of the soil microbes was also determined using the Shannon-Weaver and Evenness diversity indices. The diversity of the soil microbial population changed over the stages of plant growth, according to cluster analysis. Bacterial abundance and diversity were higher at 4 and 8 weeks after planting (WAP). The microbial abundance (richness index) in this study ranged from 0.64 to 0.94 with cultivar VL2 at 8 WAP being the highest while bulk soil (control), R2 was the lowest. The Shannon-Weaver index varied between 2.19 and 4.00 with the lowest corresponding to control while the highest was VL2 at 8 WAP. Carbon sources utilised by bacterial communities spread across the 96 carbon sources. The highest utilisation of carboxylic acids, ester, amino acids and polymers and carbohydrates was found in the bacterial communities of the different landraces across growth stages. The highest utilisation of alcohols, amides, amines, aromatic chemicals, brominated chemicals and phosphorylated chemicals was found in the control landraces. This indicates that the soil samples between 4 WAP and 12 WAP were richer in diversity of microbial species and their abundance. This soil diversity and richness is an indicator of the quality of the soil in order to increase crop yields and agricultural production.